India’s Vaccine Diplomacy and Global Health Governance: A Soft Power Approach in the Context of Public Policy and Religious Values - Joyprokash Mondal (Religion and Policy Journal, 2024)
Research Problem: India's vaccine diplomacy during the Covid-19 pandemic has not only emerged as a significant tool of soft power but also involves moral and ethical dimensions closely tied to religious values and public policy. In the midst of a global crisis, the interaction between India’s vaccine diplomacy and the religious and public policy frameworks of recipient nations requires deeper exploration.